Socioaffective parenthood and families today - Montagna, Plinio (2016)
The purpose of this paper is to discuss issues related to multiparentality in the current society, which emerges from contemporary changes originated on the second half of the 20th Century, with the increase of legal divorces that occurred. The approach to the topic is given by analyzing the origin and the concept of the term parentality, native of the French language. The theme is studied also through the consideration of maternal and paternal roles, related or not to biological genders of father and mother. The work is original when it regards, in clinical observations, the necessity of the elaboration of mourning for the loss of internal objets in order to appropriate the positive contigencies of multiparentality